Development of palm puree from different Tenera breeds and its effect on the stability, physico-chemical properties and acceptability of biscuit / Haswani Maisarah Mustafa - Mustafa, Haswani Maisarah (2014)
The health-promoting benefits and natural goodness of new developed food product of Palm Puree (PP) which is associated with antioxidant properties provide new information on its uses in food applications. Two Tenera breeds from Elaeis guineensis Jacq. oil palm fruit species were used in the preparation of PP, namely T24 and T99. Percentage yield of mesocarp of breed T24 was found to be significantly higher (p<0.05) than T99. Each breed was formulated with two different PP formulations which consist of 2% mesocarp fibre with 98% crude palm oil (formulation A) and 5% mesocarp fibre with 95% crude palm oil (formulation B). Four formulations were developed and labeled as PP24A, PP24B, PP99A and PP99B. This study consists of two phases. The first phase is to develop canned PP and determine the antioxidant properties, physico-chemical characteristics and shelf-life stability. The samples were investigated for their antioxidant properties by using various assays such as Total Phenolic Content (TPC), Total Flavonoid Content (TFC), Total Carotenoid Content (TCC), Ferric Reducing Antioxidant Power (FRAP), 1,1- diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity and Oxygen Radical Absorption Capacity (ORAC). The second phase was to develop biscuit from PP24A and PP24B which were stored for 12 weeks at room temperature and study on physico-chemical properties which includes shelf-life stability and sensory characteristics were conducted. The results revealed that both formulations of PP from T24 (PP24A and PP24B) exhibited significantly higher (p<0.05) TPC and TFC than formulations of PP from T99 (PP99A and PP99B). However, TCC of PP99A and PP99B were found significantly higher (p<0.05) than PP24A and PP24B. TPC and TFC of PP24A and PP24B also showed strong correlations with FRAP and free radical scavenging activity with values significantly higher (p<0.05) than PP99A and PP99B. The quantitative analysis for phenolic acids showed the presence of gallic, phydroxybenzoic, caffeic, vanillic, syringic, coumaric and ferulic. While four vitamin E derivatives identified were a-Tocopherol (a-T), a-Tocotrienol (01-T3), y-Tocotrienol (y-TO and 8-Tocotrienol (8-T3). Shelf-life study on all canned PP showed to be microbiologically safe with good oxidative stability throughout 12 months of storage. Five formulations which consist of biscuit without addition of PP (control or FI), biscuit added with 5% PP24A (PP24A-5or F2), biscuit added with 10% PP24A (PP24A-10 or F3), biscuit added with 5% PP24B (PP24B-5 or F4) and biscuit added with 10% PP24B (PP24B-10 or 5) were developed. The results revealed that FI exhibited lowest (p<0.05) oxidative stability compared to other formulations. However, all biscuits incorporated with PP were able to maintain their oxidative stability until 12 weeks of storage period. All PP biscuits were able to show better microbial stability compared to control biscuit until 12 weeks of storage. The physical analysis also demonstrated a decreased in L*, a* and b* values and an increased in pH values in all biscuit formulations. From the sensory evaluation, PP biscuits were accepted by the panelists and comparable to FI. Hence, the newly developed PP can be a potential source of natural food antioxidant and functional ingredient which can be incorporated in bakery product such as biscuit.